2020
DOI: 10.3390/quat3020018
|View full text |Cite
|
Sign up to set email alerts
|

The Role of El Niño in Driving Drought Conditions over the Last 2000 Years in Thailand

Abstract: Irregular climate events frequently occur in Southeast Asia due to the numerous climate patterns combining. Thailand sits at the confluence of these interactions, and consequently experiences major hydrological events, such as droughts. Proxy data, speleothem records, lake sediment sequences and tree ring chronologies were used to reconstruct paleo drought conditions. These trends were compared with modelled and historic El Niño Southern Oscillation (ENSO) data to assess if the ENSO climate phenomena is causin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Zhao et al showed that ENSO has a good ability to monitor drought and plays an important role in drought resistance and disaster reduction [48]. Katherine et al showed that the ENSO climate phenomenon could affect the drought situation in Thailand to a certain extent [49]. Xing et al studied ENSO cold and warm events and found that ENSO could easily lead to drought, and identified According to cross wavelet energy spectrum and condensation spectrum, ENSO has the greatest influence on meteorological drought, and NAO has the least influence on meteorological drought.…”
Section: Driving Factor Studymentioning
confidence: 99%
“…Zhao et al showed that ENSO has a good ability to monitor drought and plays an important role in drought resistance and disaster reduction [48]. Katherine et al showed that the ENSO climate phenomenon could affect the drought situation in Thailand to a certain extent [49]. Xing et al studied ENSO cold and warm events and found that ENSO could easily lead to drought, and identified According to cross wavelet energy spectrum and condensation spectrum, ENSO has the greatest influence on meteorological drought, and NAO has the least influence on meteorological drought.…”
Section: Driving Factor Studymentioning
confidence: 99%
“…The ENSO-induced variability in precipitation, resulted in the great flood of Thailand in 2011 due to high precipitation during strong La Niña (Gale and Saunders 2013). In contrast, during El Niño, the positive phase of the IOD (pIOD), and the ENSO neutral condition, dramatic declines in precipitation and droughts have been reported (Kim et al 2020;Power et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, abnormally low rainfall or droughts over Thailand may not be a direct consequence of a global climate condition, such as ENSO. Research has indicated that droughts in this region can occur in both El Niño and neutral ENSO events (Power et al ., 2020). Therefore, information from the ENSO phenomena alone is not sufficient to explain the variability of rainfall in Thailand.…”
Section: Introductionmentioning
confidence: 99%